Risk groups and maternal-neonatal complications of preeclampsia: current results from the national German Perinatal Quality Registry - Schneider, Sven; Freerksen, Nele; Maul, Holger; Röhrig, Silke; Fischer, Burkhard; Höft, Birgit (Journal of perinatal medicine, 2011)
Aims: We investigated risk factors and neonatal outcomes of preeclampsia. Methods: We analyzed data of the German Perinatal Quality Registry 2006 that contains the complete national birth cohort of 668,085 newborn infants and 647,392 mothers from 917 German obstetric clinics. Results: The prevalence of preeclampsia in 2006 was at 2.31%. Higher maternal age, gestational diabetes, no previous as well as multiple births, pre-pregnancy obesity and above-average weight gain during pregnancy were significantly associated with preeclampsia. A positive relationship between social burden (e.g., low social status, psychosocial stress) and the risk of preeclampsia appeared. Smoking appeared to be negatively correlated. Neonatal complications associated with preeclampsia in the study were small babies, acute respiratory distress syndrome, postpartum neonatal hypoglycemia and low Apgar scores. We did not observe an increased rate of stillbirths with preeclampsia pregnancies. Conclusions: Further studies and interventions regarding prenatal care should not focus only on how better diagnostic and treatment procedures can be implemented but also on how these diagnostic and treatment procedures can reach high-risk groups.